Predikce cen zemního plynu v závislosti na jeho zásobách - Polách, Jiří; Virglerová, Zuzana (Univerzita Pardubice, 2013)
Natural gas as well as oil is the key energy resources in the world. This fuel is one of the exhaustible and non-renewable energy sources. The fact is that someday it will come to its exhaustion. Declining offer probably will cause the increasing gas prices. The aim of this paper is to predict possible further development of the price of natural gas according to its historical development stocks. The partial aim is to determine the degree of dependence of natural gas prices on its stocks. Firstly, the analyzed gas extraction by using the SWOT analysis and the analysis of supply and demand for gas are realized. On the supply side, the states with the largest reserves of natural gas are defined. On the demand side, the biggest consumers of natural gas are identified. The dependence between two quantitative variables (the average price of natural gas and proven reserves of gas in each year since 1984) is further investigated by using correlation analysis. The price determined on the basis of historical development of the above variables is predicted by using polynomials. In conclusion, the comparison of results with analyzes of renowned institutions is accomplished.
Prediction of natural gas prices depending of its reserves
Keywords: gas; consumption; supply; price; economic